Formulasi Hukum dalam Paradigma Perubahan Masyarakat - Nadya Racheliana Liauw; I Made Sarjana (Universitas Pahlawan Tuanku Tambusai, 2023)
Law has the strategic position to organize, manage and fulfill the peace and orderliness as well as law enforcement of right and justice for human life. With the changes of law dimension formulation within a changed-society, ideal expectation and demand of law existence role should be the same, never change. The objective of this writing is in relation with law formulation that can fulfill society hope in applying sociological juridicial method. From the research, it revealed that there was a difficulty in implementing formal law (state) when facing truth claim and achievement in standard sense of justice expected by society. Because formal law is dominated by the spirit of positivism paradigm as part of free oriented value or elements reality free. The negation of contradictory or conflict of interest between the state and society are still in existence in any scale. As a result, there is no fair law enforcement and justice that is expected from the society. Therefore, an alternative solution with paradigm flexibility is indeed required instead of getting trapped in a rigid classical paradigm that has a tendency of simplification. Keywords: Law Formulation, Society Change, Conflict of Interest Harmonization.